1981
DOI: 10.1071/ea9810618
|View full text |Cite
|
Sign up to set email alerts
|

Promalin promotes lateral shoot development of young cherry trees

Abstract: Promalin (a commercial formulation of N-(phenylmethy1)-1 H-purin-6-amine plus gibberellins A4 + A7) applied at bud swell and bud burst increased the number of spurs and lateral shoots on one-year-old wood of primary scaffold limbs of young cherry trees. Painted applications gave more consistent responses than sprayed applications. Total length of shoot growth on treated three-yearold cherry trees was more than double that of control trees and lateral shoots induced by Promalin had broad crotch angles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Results from other studies indicate that cytokinin-GA products are effective for inducing sweet cherry buds to grow into shoots (Elfving and Visser, 2006;Jacyna and Puchała, 2004;Miller, 1983;Veinbrants and Miller, 1981). Results of the trials reported here…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Results from other studies indicate that cytokinin-GA products are effective for inducing sweet cherry buds to grow into shoots (Elfving and Visser, 2006;Jacyna and Puchała, 2004;Miller, 1983;Veinbrants and Miller, 1981). Results of the trials reported here…”
Section: Discussionmentioning
confidence: 51%
“…Proprietary mixtures containing the cytokinin 6-benzyladenine (BA) and gibberellic acid isomers GA 4+7 [Promalin (PR) or Perlan (PER)] can induce sylleptic shoot formation on the current season's shoots when applied during active shoot growth in both apple and cherry (Cody et al, 1985a,b;Visser, 2005, 2006;Hrotkó et al, 1999;Jacyna, 2002;Neri et al, 2003;Wustenberghs and Keulemans, 1999), but few reports document the efficacy of such products for inducing shoot development from preexisting buds on 1-year-old or older wood in sweet cherry. Miller (1983) and Veinbrants and Miller (1981) reported that painting PR onto the entire surface of 1-year-old shoots of young sweet cherry trees produced some stimulation of branch development from lateral buds. Jacyna and Puchała (2004) and Jacyna et al (1989) reported improvement in branch development and in shoot distribution when BA combined with GA 3 or GA 4+7 was painted on the lower two-thirds of 'Regina' sweet cherry branches or the central 30 cm of 'Bing' 1-year-old branches.…”
mentioning
confidence: 99%
“…Sweet cherry trees exhibit strong apical dominance, naturally producing a vigorous, upright growth habit with limited lateral branching in young trees (Miller, 1983;Veinbrants and Miller, 1981). Heavy pruning is often employed to induce lateral branch development, but this practice stimulates vigor and delays economic returns.…”
mentioning
confidence: 99%
“…Promalin Ò has been used for breaking seed dormancy (Socolowski and Cicero, 2011) and promoting plant growth (Emongor et al, 2004;Goenaga, 2010;Rossi et al, 2004). Furthermore, this product has been reported to promote shoot growth in cherry trees through an increase in cell division and expansion (Veinbrants and Miller, 1981).…”
mentioning
confidence: 99%